Peluang dan Tantangan Pendidikan Anak pada Era Pandemi bagi Wanita Karier di IAIN Bone - Niar, Astrid Rahayu (Program Studi Manajemen Pendidikan Islam IAIN Bone, 2022)
This research discusses the opportunities and challenges of children’s education in the pandemic era for career women at IAIN Bone. This study aims to understand the opportunity for children’s education in th pandemic era for career women in IAIN Bone and the challenges of children’s eduacation in the pandemic era for career women in IAIN Bone. This research is a field research with qualitative research, using pedagogical and psychological approaches using observation data collection methods, interviews, and documentation. Data collection techniques and data analysis use data clots as well as data reduction, data presentation, and conclusion drawings.The results showed that the first child education for women was because it made a necessity and more oppurtunities to be familiar with children to spend time together with shared sports, eating together, learning together, even gardening together. Parents better understand the child’s character and intellectual abilities of children, children can master learning with technology. Second, one the other hand, child psychological burden increases because it is often burdened with various tasks of the subjects that accumulate, for example when in one day there are three subjects, there are three tasks given by educators with the same deadline so sometimes making saturated children in learning.